Pemberdayaan Masyarakat Wonorejo Melalui Pelatihan Pembuatan Cymbosavon (Handwash Serai Wangi) sebagai Upaya Penguatan Ekonomi Masyarakat - Henny Parida Hutapea; Niken Trisnawati; Mikhael Krisnaputra; Yasintha Eka Yuliana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This community service activity aims to improve the welfare and economic independence of Wonorejo Village residents through training in making herbal hand soap from citronella named Cymbosavon. The activity was motivated by the low utilization of local potential and limited community skills in processing citronella into products with sales value. The methods used include field observation, problem identification, and intensive training on production processes, packaging, and product marketing strategies. The results of the activity showed an increase in the technical skills of residents in making hygienic and environmentally friendly liquid soap, as well as the emergence of entrepreneurial awareness. This program is expected to trigger the formation of sustainable local business units and encourage the optimization of village natural potential in the context of inclusive economic development.